Rural Non-Agricultural Working Force and Levels of Development in Uttar Pradesh: A Regional Analysis (India) - ., Shafiqullah; Asma, Sana (Asian Review of Environmental and Earth Sciences, 2015)
The present paper investigate the trends of rural non-agricultural working force over the period of 1971 to 2011, the regional variations in the rural non-agricultural working force and the relationship between rural non-agricultural working force and levels of development among the districts of Uttar Pradesh. The regional variations in the distribution of workforce in rural non-agricultural sectors are quite notable. The general picture emerged that there is a gradual increase of main workforce in non-agricultural sector from north-western to south-eastern parts of Uttar Pradesh. The distribution of female main workforce in non-agricultural workforce depicts that there is a gradual decrease from west to south-east. The statistical analysis leads to conclusion that agriculture, population growth and health facilities are the chief determinants but the magnitudes of their effects are dissimilar.